Impact of Insulin-Sensitizing Agents on Reproductive Function in Women with Polycystic Ovary Syndrome - Korba, Magdalena; Tłustochowicz, Katarzyna; Malicka, Natalia; Łuczak, Karolina; Krajewska, Agnieszka; Polkowska, Wiktoria; Kowalik, Adrianna; Korzeniewska, Agnieszka; Dębczak, Julia (Journal of Education, Health and Sport, 2026)
Background. Polycystic ovary syndrome (PCOS) is a common endocrine disorder in women of reproductive age, which collectively impair fertility. Insulin-sensitizing agents have emerged as a key therapeutic strategy to improve metabolic, hormonal, and reproductive outcomes in this population. Aim. This review critically evaluates current evidence on insulin-sensitizing agents in women with PCOS, addressing both their mechanisms of action at the metabolic and ovarian levels and their effects on reproductive outcomes. Material and Methods. A review of randomized controlled trials, meta-analyses, and high-quality observational studies published up to 2025 evaluated the effects of metformin, myo-inositol, and berberine on reproductive outcomes in women with PCOS. Results. Insulin-sensitizing agents improve metabolic dysfunction and ovulatory outcomes in PCOS. Metformin increases ovulation and clinical pregnancy rates, particularly in women with insulin resistance or higher BMI, though its effect on live birth is inconsistent. Myo-inositol and berberine show beneficial effects on metabolic parameters and ovulatory function, but evidence for live birth and miscarriage remains limited. Conclusions. Insulin-sensitizing therapies support reproductive function in women with PCOS, particularly in metabolically compromised phenotypes. Metformin has the strongest evidence base, whereas myo-inositol and berberine are promising adjunctive or alternative options. Future high-quality randomized trials focusing on live birth and miscarriage outcomes, standardized reporting, and precise patient stratification are needed to optimize the clinical use of these agents in PCOS-related infertility.